Factors associated with self-perceived stress, anxiety, and depression in school teachers during the COVID-19 pandemic: analysis of a Peruvian national survey - Tapia Sequeiros, Gustavo (2026)
Objective: To explore factors associated with self-perceived stress, anxiety, and depression in Peruvian school teachers during the COVID-19 pandemic. Methods: A cross-sectional analytical study was conducted using data from the National Teacher Survey (ENDO) of 2021. Public school teachers at the preschool, elementary, and secondary levels in Peru were included. Associated factors were assessed by estimating prevalence ratios with a 95% confidence interval using Poisson regression with robust variance. Results: The final analyzed sample included 9,765 teachers. The main self-perceived mental health problem was stress (55.8%), followed by anxiety (28.4%) and depression (19.1%). Stress was associated with female gender (aPR: 1.06; 95% CI: 1.04–1.09) and responsibility for the care of a vulnerable person (aPR: 1.02; 95% CI: 1.01–1.05). Anxiety was associated with residing in urban areas (aPR: 1.03; 95% CI: 1.01–1.05) and having three or more comorbidities (aPR: 1.33; 95% CI: 1.29–1.38). Depression was associated with female gender (aPR: 1.04; 95% CI: 1.02–1.06) and being responsible for a vulnerable person (aPR: 1.05; 95% CI: 1.03–1.07). Conclusions: Stress was the primary self-perceived mental health problem. Several factors associated with stress, anxiety, and depression were identified. Therefore, the implementation of intervention strategies focused on teachers’ mental health is recommended.